PENGARUH MOTIVASI TERHADAP PRODUKTIVITAS KERJA PADA PROYEK REVITALISASI RUMAH SUSUN GUDMURA PALDAM KOTA AMBON (Menara: Jurnal Teknik Sipil, 2023)
This study aims to determine the Effect of Motivation on Work Productivity in the Gudmura Paldam Flats Revitalization Project in Ambon City. The method used in this study is quantitative analysis method. Subjects in this study were 20 samples. Primary data collection techniques through questionnaires and secondary data collection through literature research. While the data analysis methods used are quantitative descriptive data analysis, validity test, reliability test, f test (anova), t test. The results show, based on the t test as follows: 1. The need obtained t-count -1.937 > t-table 2.101 and the probality value sig 0.071 > 0.05 then the decision taken HO accepted and HI rejected. 2) Environment obtained t-count 2,296 > t-table 2,101 and the probality value was sig 0.036 > 0.05 then the decision taken by HO rejected and HI accepted. 3) Workers' wages obtained t-1,559 < 2,101 and the probality value was sig 0.139 > 0.05 then the decision taken was HO accepted and HI rejected. The motivation variable has a positive and significant effect on the environment because the t-count value is obtained 2,296 > t-table 2,101 and the probality value is sig 0.036 > 0.05 it has an influence on work productivity.